Design and Verification of Self-organized Communication Network for Micro UAV Swarms - XIAO Huihui; HE Yilin; HU Xiaodong; DENG Yang (Kongzhi Yu Xinxi Jishu)
Based on the characteristics analysis of UAV swarms communication, a self-organized information transmission scheme based on graph theory was designed. According to the transmission distance, transmission rate and reliability requirements of UAV swarms communication, the communication hardware nodes based on Jenic5148-001-M04 and the corresponding network node control software based on Eclipse Platform were developed. Test results verify the rationality of the information transmission scheme and the availability of the self-organized communication network nodes, which provides a way for communication realization of micro UAV swarms.